Atomic force microscopy combined with human pluripotent stem cell derived cardiomyocytes for biomechanical sensing - Pesl, Martin; Pribyl, Jan; Acimovic, Ivana; Vilotic, Aleksandra; Jelinkova, Sarka; Salykin, Anton; Lacampagne, Alain; Dvorak, Petr; Meli, Albano C; Skladal, Petr; Rotrekl, Vladimir (Biosensors & bioelectronics, 2016)
Cardiomyocyte contraction and relaxation are important parameters of cardiac function altered in many heart pathologies. Biosensing of these parameters represents an important tool in drug development and disease modeling. Human embryonic stem cells and especially patient specific induced pluripotent stem cell-derived cardiomyocytes are well established as cardiac disease model.. Here, a live stem cell derived embryoid body (EB) based cardiac cell syncytium served as a biorecognition element coupled to the microcantilever probe from atomic force microscope thus providing reliable micromechanical cellular biosensor suitable for whole-day testing. The biosensor was optimized regarding the type of cantilever, temperature and exchange of media; in combination with standardized protocol, it allowed testing of compounds and conditions affecting the biomechanical properties of EB. The studied effectors included calcium , drugs modulating the catecholaminergic fight-or-flight stress response such as the beta-adrenergic blocker metoprolol and the beta-adrenergic agonist isoproterenol. Arrhythmogenic effects were studied using caffeine. Furthermore, with EBs originating from patient's stem cells, this biosensor can help to characterize heart diseases such as dystrophies.
Keywords: biomechanika; Adrenergic beta-1 Receptor Antagonists; Myocardial Contraction; buněčné kultury; buněčné linie; biosenzitivní techniky; preklinické hodnocení léčiv; mikroskopie atomárních sil; agonisté adrenergních beta-receptorů; design vybavení; Isoproterenol; Biosensing Techniques; isoprenalin; Myocytes, Cardiac; pluripotentní kmenové buňky; Metoprolol; kardiomyocyty; kontrakce myokardu; Pluripotent Stem Cells; Cell Line; Drug Evaluation, Preclinical; antagonisté beta-1-adrenergních receptorů; metoprolol; Biomechanical Phenomena; Microscopy, Atomic Force; lidé; Adrenergic beta-Agonists; Cell Culture Techniques; Humans; Equipment Design